2011
DOI: 10.1093/cercor/bhr298
|View full text |Cite
|
Sign up to set email alerts
|

White Matter Network Abnormalities Are Associated with Cognitive Decline in Chronic Epilepsy

Abstract: Patients with chronic epilepsy frequently display cognitive comorbidity and might have widespread network abnormalities outside the epileptic zone, which might affect a variety of cognitive functions and global intelligence. We aimed to study the role of white matter connectivity in cognitive comorbidity. Thirty-nine patients with nonsymptomatic localization-related epilepsy and varying degrees of cognitive impairment and 23 age-matched healthy controls were included. Whole brain white matter networks were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
128
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(136 citation statements)
references
References 49 publications
8
128
0
Order By: Relevance
“…Focal epilepsy is increasingly being recognized as both a gray and white matter disease (Otte et al 2012b;Gross 2011;Salmenpera and Duncan 2005;McMillan et al 2004;Seidenberg et al 2005;Vaessen et al 2011). Nevertheless, how and to what extent focal epilepsy affects the global brain white matter is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Focal epilepsy is increasingly being recognized as both a gray and white matter disease (Otte et al 2012b;Gross 2011;Salmenpera and Duncan 2005;McMillan et al 2004;Seidenberg et al 2005;Vaessen et al 2011). Nevertheless, how and to what extent focal epilepsy affects the global brain white matter is largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Others studies have provided evidence that focal epilepsy is a large brain network disease [for review see (Stam and van Straaten 2012)]. Interestingly, a recent study that applied structural whole brain network analysis to individuals with chronic TLE revealed impaired white matter networks, while white matter volume was preserved (Vaessen et al 2011). Evidently, more research is needed to elucidate how focal epilepsy affects white matter in general and its volume in particular.…”
Section: Focal Epilepsymentioning
confidence: 99%
“…29,30 The WM tracts connecting the frontal lobe to the temporal and occipital lobes have demonstrated smaller volumes in children with FLE compared with controls, 34 indicating impaired structural connections between the frontal and temporal and occipital lobes. Vaessen et al 4 found that the clustering coefficient was significantly positively correlated with IQ, and path length was negatively correlated with IQ in adults with cryptogenic localizationrelated epilepsy. In that study, 4 the patients had a broader range of IQ scores including those who are nonimpaired (mean IQ of 97) and those who are impaired (mean IQ of 85).…”
Section: Discussionmentioning
confidence: 99%
“…Vaessen et al 4 found that the clustering coefficient was significantly positively correlated with IQ, and path length was negatively correlated with IQ in adults with cryptogenic localizationrelated epilepsy. In that study, 4 the patients had a broader range of IQ scores including those who are nonimpaired (mean IQ of 97) and those who are impaired (mean IQ of 85). In a subsequent study, 10 the same authors did not find an association between the clustering coefficient and path length measures of structural or functional connectivity with a computerized visual searching task in children with FLE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation